2023
DOI: 10.3389/fmed.2023.1164394
|View full text |Cite
|
Sign up to set email alerts
|

Case report: A case of incontinentia pigmenti

Abstract: Incontinentia pigmenti (IP) is a rare neuroectodermal dysplasia caused by mutations in the IKBKG gene. We present a case of a 4-month-old female infant with erythematous vesicular skin lesions on the trunk and extremities. Histopathologic examination of the blisters revealed an eosinophilic infiltrate. Further investigation revealed that her mother had three unexplained miscarriages and two normal uncomplicated pregnancies, resulting in the birth of two male infants. We performed a comprehensive genetic evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…NF-κB plays an important role in regulating cell proliferation, apoptosis, and inflammation. When IKBKG is not correctly expressed, cells become sensitive to apoptotic signals, leading to the development of various inflammatory responses that are particularly active in ectodermal cells ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NF-κB plays an important role in regulating cell proliferation, apoptosis, and inflammation. When IKBKG is not correctly expressed, cells become sensitive to apoptotic signals, leading to the development of various inflammatory responses that are particularly active in ectodermal cells ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are few relevant studies on the causes of IP recurrence, and it has been reported that some IKBKG -deficient keratinocytes can survive through escape; however, residual IKBKG -deficient keratinocytes that manage to escape and survive the elimination process can undergo second episodes of the first stage of IP owing to the reoccurrence of keratinocyte hyperproliferation and subsequent inflammatory reactions ( 6 , 7 ). The vesicular phase usually disappears within four to 6 months ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation